Political Leaders Communication: A Twitter Sentiment Analysis during Covid-19 Pandemic - Kaur, Manpreet; Verma, Rajesh; Ranjan, Sandeep (Universitas Semarang, 2021)
The pandemic made it critical for political leaders to intensify measures in fight against Covid-19 and one such measure was building trust among public through communication. With exponential growth in reach of social media, while state political leaders have progressively used internet for election campaigns, limited studies have explored as to how leaders use this medium to communicate during crisis, what kind of information do they share and what are common issues addressed. This paper, using qualitative research design, analyses Indian political leaders communication on Twitter. Sentiment Analysis was carried to identify and extract subjective information in leaders communication using 29 Indian political leaders, where in 12.128 tweets were extracted. Subjectivity scores depicted more than half of leaders had shared fact-based information, and Polarity scores indicated that almost 90% of leaders shared positive or neutral information thus leading to an inference that leaders share more of facts based and positive or neutral information rather than statements in form of opinions.